2009
DOI: 10.1007/s12098-009-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of attention-deficit/hyperactivity disorder on health-related quality-of-life of specific learning disability children

Abstract: Co-occurring ADHD adversely impacts the HRQOL of children with newly diagnosed SpLD especially in domains related to their psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
2
12
1
1
Order By: Relevance
“…Our study extends several aspects of the existing, but very limited data on the QoL of children with an RD (Karande et al, 2009; Karande and Bhosrekar, 2009; Rotsika et al, 2011; Karande and Venkataraman, 2012, 2013; Ginieri-Coccossis et al, 2013). …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our study extends several aspects of the existing, but very limited data on the QoL of children with an RD (Karande et al, 2009; Karande and Bhosrekar, 2009; Rotsika et al, 2011; Karande and Venkataraman, 2012, 2013; Ginieri-Coccossis et al, 2013). …”
Section: Discussionsupporting
confidence: 80%
“…There are only limited and controversial data on the impact of comorbidity on the QoL of children with RD (Karande and Bhosrekar, 2009; Karande and Venkataraman, 2013). Karande and Bhosrekar (2009) reported that parent-rated QoL of children with SpLD and comorbid ADHD was significantly poorer than for children with SpLD but without comorbid ADHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further detailed analysis of our results confirmed that the HRQoL of children with newly diagnosed SpLD and co-occurring ADHD (SpLD/ADHD) was significantly poorer than the HRQoL of "SpLD only" children (Karande and Bhosrekar 2009). Our data clearly showed that "SpLD/ADHD" children more often exhibit aggressive, immature, and delinquent behavior; they are more dissatisfied with their abilities, family and peer relationships, and their overall life; and their problems have a significant impact on their parent's emotional health and personal time.…”
Section: Health-related Quality Of Life (Hrqol) Of Children With Spldsupporting
confidence: 62%
“…The children with SpLD/ ADHD need special care as they and their parents have far more problems in their everyday life than children with SpLD only (Karande and Bhosrekar 2009). To improve QoL of children with SpLD/ADHD, it is important to treat co-occurring ADHD effectively (by behavioral therapy and if necessary with medications) to improve the psychosocial health of such children.…”
Section: Improving Qol Of Indian Children With Spldmentioning
confidence: 99%